2008
DOI: 10.1097/ta.0b013e3181826ddf
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Outcomes in Damage Control Resuscitation: Identifying Blood Product Ratios Associated With Improved Survival

Abstract: Increased FFP:PRBC and PLT:PRBC ratios during a period of massive transfusion improved survival after major trauma. Massive transfusion protocols should be designed to achieve these ratios to provide maximal benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
213
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(222 citation statements)
references
References 19 publications
6
213
0
3
Order By: Relevance
“…Several retrospective cohort studies have found substantial survival gains with this approach in both military 45 and civilian [46][47][48] trauma settings. More recently, however, other investigators 49 have not confirmed this finding when applying statistical techniques to correct for immortal time bias.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective cohort studies have found substantial survival gains with this approach in both military 45 and civilian [46][47][48] trauma settings. More recently, however, other investigators 49 have not confirmed this finding when applying statistical techniques to correct for immortal time bias.…”
Section: Discussionmentioning
confidence: 99%
“…22 This area of debate is likely to continue until a prospective randomized trial is completed. 1,[4][5][6][7]9 Although the technique of perihepatic packing was founded in 1908 with Pringle's discussion of hepatic trauma, 43 the modern interpretation of this work occurred in the late 1970s, [44][45][46] followed by the concept of truncated operations with concurrent intra-abdominal packing for patients in physiologic extremis by Stone and colleagues in 1983. 47 This philosophy was then coined "damage control" by Rotondo and colleagues, given its obvious conceptual similarity to the Navy's use of the same term.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] While the effect on overall mortality in the civilian population is still debated, [21][22][23][24] massive resuscitations with high plasma:packed red blood cell (RBC) ratios remain promising for addressing the early coagulopathy 25 and acidosis frequently associated with life-threatening injury. 10 Additional benefits of a formal MTP include earlier administration of blood products during the resuscitation phase, improved overall efficiency, decreased total blood product use during a patient's hospital stay and a substantial economic savings.…”
mentioning
confidence: 99%
“…18,19 Des études rétrospectives menées dans des hôpitaux militaires en zone de combat et des centres de traumatologie ont montré une association entre l'augmentation des ratios plasma/globules rouges et l'amélioration de la survie. [18][19][20][21][22][23][24] Néanmoins, des patients recevant des ratios transfusionnels élevés de plasma congelé/globules rouges ont eu un risque plus élevé de complications infectieuses, un plus grand nombre de jours sous ventilateur et un séjour prolongé aux soins intensifs. 25 En outre, le Comité national consultatif canadien sur le sang et les produits sanguins a publié un consensus élaboré au cours de la Conférence de consensus sur la transfusion massive qui s'est tenue à Toronto en juin 2011: le biais de survie constitue un obstacle majeur pour une interprétation correcte des associations faites rétrospectivement entre les ratios transfusionnels et le pronostic du traumatisme; par ailleurs, nous ne disposons actuellement que de données scientifiques limitées à l'appui de protocoles transfusionnels reposant sur des ratios (par exemple, un ratio d'unités de globules rouges/plasma/plaquettes de 1:1:1).…”
Section: Syndrome Respiratoire Aigu Post-transfusionnelunclassified
“…18,19 Retrospective studies from combat hospitals and trauma centres have found an association between increased plasma-to-RBC and platelet-to-RBC transfusion ratios and improved survival. [18][19][20][21][22][23][24] Nevertheless, patients receiving high frozen plasma-RBC transfusion ratios were at higher risk of septic complications, an increased number of ventilator days, and increased length of stay in the intensive care unit. 25 Further, the Canadian National Advisory Committee on Blood and Blood Products has published a consensus developed at the Massive Transfusion Consensus Conference (June 2011, Toronto, Canada) that survivorship bias comprises a major obstacle in the proper interpretation of retrospective associations between transfusion ratios and trauma outcome, and limited scientific evidence currently exists to support ratio-driven (e.g., 1:1:1 ratios of RBC, plasma, and platelet units) transfusion protocols.…”
Section: Management Of Massive Transfusion In the Trauma Settingmentioning
confidence: 99%